Nitrogen addition promotes the transformation of heavy metal speciation from bioavailable to organic bound by increasing the turnover time of organic matter: An analysis on soil aggregate level. (December 2019) - Li, Renfei; Tan, Wenbing; Wang, Guoan; Zhao, Xinyu; Dang, Qiuling; Yu, Hanxia; Xi, Beidou
Abstract: Nitrogen (N) addition can change physicochemical properties and biogeochemical processes in soil, but whether or not these changes further affect the transport and transformation of heavy metal speciation is unknown. Here, a long-term (2004–2016) field experiment was conducted to assess the responses of different heavy metal speciation in three soil aggregate fractions to N additions in a temperate agroecosystem of North China. The organic matter turnover time was quantified based on changes in δ 13 C following the conversion from C3 (wheat) to C4 crop (corn). Averagely, N addition decreases and increases the heavy metal contents in bioavailable and organic bound fractions by 27.5% and 16.6%, respectively, suggesting N addition promotes the transformation of heavy metal speciation from bioavailable to organic bound, and such a promotion in a small aggregate fraction is more remarkable than that in a large aggregate fraction. The transformations of heavy metal speciation from bioavailable to organic bound in all soil aggregate fractions are largely dependent on the increments in the turnover time of organic matter. The increase in organic matter turnover time induced by N addition may inhibit the desorption of heavy metals from organic matter by prolonging the interaction time between heavy metals and organic matter and enhance the capacity of organic matter to adsorb heavy metals by increasing the humification degree and functional group. Our work can provide insights into the accumulation, migration, and transformation of heavy metals in soils in the context of increasing global soil N input from a microenvironmental perspective. Graphical abstract: Image 1 Highlights: We presented the first linking between soil N inputs and the transport and transformation of environmental contaminants. The chemical fractionation of heavy metals in different soil aggregate fractions were investigated. The SOM turnover time of different soil aggregate fractions were investigated. Nitrogen addition promoted the transformation of HM speciation from bioavailable to organic bound. Abstract : Main finding: Nitrogen addition promotes the transformation of heavy metal speciation from bioavailable to organic bound.